Denial of a sleep deprivation message: situational and dispositional influences on message rejection. - Thompson, Suzanne; Marber, Haley; Cornejo, Laeesha; Launer, Bryn; Ayala, Kimberly (Journal of Behavioral Medicine, 2017)
Two studies investigated situational and dispositional influences on rejection of a sleep deprivation warning message for young adults. The hassle of protection (Study 1) and the self-relevance of the problem (Study 2) were manipulated; the disposition to use denial (threat orientation) for warning messages was measured. In both studies, it was found that both dispositional denial and the situational manipulation (more protection-hassle or self-relevance) showed at least one denial effect by reducing perceived susceptibility, perceived severity, or credibility. Indirect (mediational) effects were tested with the bootstrap method. In Study 1, judgments of credibility and severity mediated the effects of the hassle manipulation and denial orientation on message outcomes. In Study 2, credibility mediated the effects of the self-relevance manipulation and denial orientation on message outcomes of intentions to change and priority given to sleep. These studies show that both situational and dispositional sources of denial work in similar ways by lowering key message judgments and that the lower judgments lead to less priority given to a health risk and lower intentions to protect oneself.